The Effect of General Allocation Funds and Local Own-Revenue on Regional Government Expenditure in Central Java Province - Samsul Afif Rahula; Prasetyo Ari Bowo (Journal of Economics and Business, 2020)
The implementation of regional autonomy indirectly requires regions to be independent, the level of independency in Central Java which is measured by the ratio of Local Own-source Revenue to total regional revenue of 18.2%, which is the lowest compared to other regions in Java in the 2015-2018 period. Central Java's low independency is in line with its dependency on transfers from the central government, particularly the general allocation fund of 40%. Low independency and high dependency is due to the lack of ability of Local Own-source Revenue to meet regional expenditures and the large role of general allocation fund in meeting these shortages. This study aims to analyze the effect of general allocation funds and local own-source revenue on regional expenditures. This study uses a quantitative method with panel data combination of cross-section data from 35 districts/cities in Central Java Province and time-series data for the period 2016-2018. The analytical method used is multiple linear regression. The results of this study indicate that the general allocation fund has a significant and more dominant positive effect on regional expenditures and also local own-source revenue shows a significant positive effect on regional expenditures, which means that the greater the value of local own-source revenue and general allocation fund, the greater the value of regional expenditures. Simultaneously, general allocation funds and local own-source revenue have a significant positive effect on regional expenditures.